The Accessory Olfactory Bulb in Arvicola scherman: A Neuroanatomical Study in a Subterranean Mammal - Sara Ruiz-Rubio; Irene Ortiz-Leal; Mateo V. Torres; Mostafa G. A. Elsayed; Aitor Somoano; Pablo Sanchez-Quinteiro (Animals)
The accessory olfactory bulb (AOB) processes chemical signals crucial for species-specific socio-sexual behaviors. There is limited information about the AOB of wild rodents, and this study aims to characterize the neurochemical organization of the AOB in the fossorial water vole (Arvicola scherman), a subterranean Cricetidae rodent. We employed histological, immunohistochemical, and lectin-histochemical techniques. The AOB of these voles exhibits a distinct laminar organization, with prominent mitral cells and a dense population of periglomerular cells. Lectin histochemistry and G-protein immunohistochemistry confirmed the existence of an antero-posterior zonation. Immunohistochemical analysis demonstrated significant expression of PGP 9.5, suggesting its involvement in maintaining neuronal activity within the AOB. In contrast, the absence of SMI-32 labelling in the AOB, compared to its strong expression in the main olfactory bulb, highlights functional distinctions between these two olfactory subsystems. Calcium-binding proteins allowed the characterization of atypical sub-bulbar nuclei topographically related to the AOB. All these features suggest that the AOB of Arvicola scherman is adapted for enhanced processing of chemosensory signals, which may play a pivotal role in its subterranean lifestyle. Our results provide a foundation for future studies exploring the implications of these adaptations, including potential improvements in the management of these vole populations.